Long noncoding RNA UFC1 acts as an oncogene via stimulating EZH2-induced inhibition of APC expression in renal cell carcinoma: LncRNA UFC1 drives the progression of renal cell carcinoma - Wang, Jinteng; Liu, Guanlin (Cellular and Molecular Biology, 2023)
This study aimed to illustrate the biological functions of long noncoding RNA (lncRNA) UFC1 in the carcinogenesis and cancer development of renal cell carcinoma (RCC), and the potential molecular mechanism. UFC1 levels in RCC tissues and cell lines were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Diagnostic and prognostic potentials of UFC1 in RCC were assessed by depicting receiver operating characteristic (ROC) curves and Kaplan-Meier curves, respectively. After transfection with si-UFC1, proliferative and migratory changes in ACHN and A498 cells were detected by cell counting kit-8 (CCK-8) and transwell assay, respectively. Subsequently, chromatin immunoprecipitation (ChIP) was conducted to examine the enrichments of EZH2 (enhancer of zeste homolog 2) and H3K27me3 in the APC promoter region. Finally, rescue experiments were carried out to identify the co-regulation of UFC1 and APC on RCC cell behaviors. The results showed that UFC1 was highly expressed in RCC tissues and cell lines. ROC curves revealed the diagnostic potential of UFC1 in RCC. Besides, survival analysis showed that highly expressed UFC1 predicted poor prognosis in RCC patients. Knockdown of UFC1 in ACHN and A498 cells attenuated cell proliferative and migratory abilities. UFC1 was able to interact with EZH2, and the knockdown of UFC1 could upregulate APC. In addition, both EZH2 and H3K27me3 were enriched in the APC promoter region, which could be blocked by the knockdown of UFC1. Moreover, rescue experiments demonstrated that the silence of APC was able to abolish the inhibited proliferative and migratory abilities in RCC cells with UFC1 knockdown. LncRNA UFC1 inhibits APC level through upregulating EZH2, thus aggravating the carcinogenesis and cancer development of RCC.